PSAS: A Framework for Peer Assessment of an Individuals Skills in a Software Projects Team - Santos, Tiago da Rosa; Kemczinski, Avanilde (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Competency assessment in a software project team allows you to identify how each individual can collaborate to achieve the success of a project. The peer assessment approach can bring better results by having the vision of more than one team member. This article proposes a framework to automate the peer assessment of people's competences in software project teams, developed and evaluated using the interaction design approach. The framework allows to create and apply peer reviews with co-assessment, 360-degree and self-assessment strategies and graphically analyze the performance of people, teams, compare the results of the assessment, identify highlights and follow trends through history.